Trade in services related to the environment - Sauvage, Jehan (OECD Trade and Environment Working Papers, 2017)
This paper discusses the nature and scope of international trade in environmentally related services, and analyses the implications that services trade restrictions have on the provisions of these services domestically and abroad. Numerous services appear crucial to the delivery and proper functioning of environmental goods and equipment be they a wastewater-treatment facility or a renewable power plant. By helping lower the costs of these services and improving access to world-class suppliers, trade policy can contribute alongside energy and environmental policy to the prevention and abatement of greenhouse-gas emissions and pollution in all its forms. Besides clarifying the role and scope of services related to the environment, the analysis undertaken in this paper suggests that the restrictions that countries impose on services trade may have a detrimental effect on the provision of environmental activities through the establishment by specialised firms of a commercial presence abroad, i.e. through mode 3 trade in services